Defect Reduction in Injection Process A Case Study of A Washing Machine by Design of Experiment - พึ่งสุข ภัคจิรา; รุ่งเรืองอนันต์ วิชัย (Frontiers in Engineering Innovation Research, 2012)
The objective of this research was to reduce the defective proportion which was up to 4.29% in the injection process of a tub part of a washing machine’s production. The researcher had collected defect data from February to June 2011, 61.1% of the entire defection was air bubble found on the surface of the washing tub. The factors and root cause of defect found by using brainstorming and why -why analysis techniques. The factors of defect were cylinder pressure in barrel and temperature access to the mold (Hot Runner). The pressure in barrel for one product injection had 5 range, PI was 35 and 45 MPa, P2 was 45 and 55 MPa, PJ was 90 and 95 MPa, P4 was 65 and 75 MPa, P5 was 60 and 65 MPa. Temperature access to the mold (Hot Runner) was 270 and 280°C For this production process had limitation of material .The appropriate operating condition of factors found by Design of Experiment using the 2k factorial design with I replicate. There were 6 factors and 64 experiments. The result showed that the appropriate of pressure conditions was 45, 45, 90, 65, 70 MPa and temperature access to mold was 280 DC After applying the appropriate operating condition to the injection process of a tub part of a washing machine’s production in August .2011, the defective rate reduced from 2.62 % to 2.02%